Single-shot velocity-map imaging of attosecond light-field control at kilohertz rate - Süßmann, F.; Zherebtsov, S.; Plenge, J.; Johnson, Nora G.; Kübel, M.; Sayler, A. M.; Mondes, V.; Graf, C.; Rühl, E.; Paulus, G. G.; Schmischke, D.; Swrschek, P.; et al. (My University, 2011)
High-speed, single-shot velocity-map imaging (VMI) is combined with carrier-envelope phase (CEP) tagging by a single-shot stereographic above-threshold ionization (ATI) phase-meter. The experimental setup provides a versatile tool for angle-resolved studies of the attosecond control of electrons in atoms, molecules, and nanostructures. Single-shot VMI at kHz repetition rate is realized with a highly sensitive megapixel complementary metal-oxide semiconductor camera omitting the need for additional image intensifiers. The developed camera software allows for efficient background suppression and the storage of up to 1024 events for each image in real time. The approach is demonstrated by measuring the CEP-dependence of the electron emission from ATI of Xe in strong (≈1013 W/cm2) near single-cycle (4 fs) laser fields. Efficient background signal suppression with the system is illustrated for the electron emission from SiO2 nanospheres.